Study of a 3×3 module array of the ECAL0 calorimeter with an electron beam at the ELSA. (13th February 2015) - Dziewiecki, M; Anfimov, N; Anosov, V; Barth, J; Chalyshev, V; Chirikov-Zorin, I; Elsner, D; Frolov, V; Frommberger, F; Guskov, A; Klein, F; Krumshteyn, Z; et al.
Abstract: ECAL0 is a new electromagnetic calorimeter designed for studying generalized parton distributions at the COMPASS II experiment at CERN. It will be located next to the target and will cover larger photon angles (up to 30 degrees). It is a modular high-granularity Shashlyk device with total number of individual channels of approx. 1700 and readout based on wavelength shifting fibers and micropixel avalanche photodiodes. Characterization of the calorimeter includes tests of particular sub-components, tests of complete modules and module arrays, as well as a pilot run of a fully-functional, quarter-size prototype in the COMPASS experiment. The main goals of the tests on low-intensity electron beam at the ELSA accelerator in Bonn were: to provide energy calibration using electrons, to measure angular response of the calorimeter and to perform an energy scan to cross-check previously collected data. A dedicated measurement setup was prepared for the tests, including a 3x3 array of the ECAL0 modules, a scintillating-fibre hodoscope and a remotely-controlled motorized movable platform. The measurements were performed using three electron energies: 3.2 GeV, 1.6 GeV and 0.8 GeV. They include a calibration of the whole detector array with a straight beam and multiple angular scans.